2020
DOI: 10.31219/osf.io/gcpq8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Effects of COVID-19 Containment Policies on Crime: An Empirical Analysis of the Short-term Aftermath in Los Angeles

Abstract: The global spread of 2019-nCoV, a new virus belonging to the coronavirus family, forced national and local governments to apply different sets of measures aimed at containing the outbreak. Los Angeles has been one of the first cities in the United States to declare the state of emergency on March 4 th , progressively issuing stronger policies involving (among the others) social distancing, the prohibition of crowded private and public gatherings and closure of leisure premises. These interventions highly disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 73 publications
4
65
3
6
Order By: Relevance
“… 2015 ), partially replicating the methodology presented in Campedelli et al. ( 2020 ). Within the context of the Bayesian models, we focus on the distribution, direction, and significance of the relative cumulative effect (RCE) of COVID-19 containment policies for each crime in each community.…”
Section: The Present Workmentioning
confidence: 80%
See 2 more Smart Citations
“… 2015 ), partially replicating the methodology presented in Campedelli et al. ( 2020 ). Within the context of the Bayesian models, we focus on the distribution, direction, and significance of the relative cumulative effect (RCE) of COVID-19 containment policies for each crime in each community.…”
Section: The Present Workmentioning
confidence: 80%
“… 2020 )—crime reduction is the prevalent spillover on crime of COVID-19 containment policies (Ashby 2020 ; Campedelli et al. 2020 ; Mohler et al. 2020 ; Payne et al.…”
Section: The Present Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For crime related calls for service he concluded that while some cities saw decreases, the over all pattern was that more than half the cities studied had levels of calls for service that were of an expected level for each crime type studied. Campedelli et al (2020) analyzed crime in Los Angeles until March 28th, and found no change to homicide, assault with deadly weapon, intimate partner violence, vehicle theft or burglary. They did however note a small reduction of assaults, and somewhat larger reductions in shoplifting, theft and robberies as well as for total crime (Campedelli et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On March 11, 2020, the World Health Organization (WHO) declared a global pandemic following the rapid spread of COVID-19 (Campedelli et al, 2020). In an attempt to spearhead agency response to COVID-19, Exit: Executives Transforming Probation & Parole, a coalition consisting of current and former community supervision executives, and the Vera Institute of Justice (2020b) released statements with recommendations for community supervision agencies across the United States.…”
Section: Literature Reviewmentioning
confidence: 99%